Potret Pertentangan Kelas Sosial dalam Novel Hello karya Tere Liye - Ananda, Gita Reski; Hasanuddin WS, Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2024)
The aim of this research is to provide a description of social class conflict, encompassing its various manifestations, contributing factors, and consequences. Qualitative methods are employed to conduct this research, incorporating descriptive techniques. The primary data and sources utilized for this study are derived from the novel Hello by Tere Liye, which delves into social class conflicts. The data collection techniques consist of a comprehensive understanding and analysis of the novel, conducting a literature review of relevant works, and gathering data specifically pertaining to social class conflicts depicted in Hello. The research findings reveal distinct forms of social class conflict, namely vertical conflict occurring within hierarchical structures, horizontal conflict arising from inequalities within families or groups of similar positions, and diagonal conflict commonly associated with the government. Furthermore, the novel identifies several factors contributing to social class conflict, including horizontal pluralism, vertical plurality, differences in beliefs and perspectives, and divergent interests. The impacts resulting from social class conflicts encompass both positive and negative outcomes. Positive impacts include functional effects that engage others in conflict resolution, stimulate economic growth, and alleviate stress, anxiety, frustration, and anger. Conversely, dysfunctional impacts involve a lack of motivation to work, personal insults, threats that undermine trust, and negative consequences.